Pendidikan pemberdayaan masyarakat desa perspektif Achmad Nuril Mahyudin - Nugraha, Ady Madya; Rosyadi, Abdu Rahmat; Handrianto, Budi (Tawazun: Jurnal Pendidikan Islam, 2023)
Indonesia is a developing country member of the United Nations (UN) which has contributed to the success of the Sustainable Development Goals (SDGs) program with several goals for the welfare and development of the nation including poverty reduction. In its implementation, the government is supported by many philanthropic institutions that focus on their respective goals. Poverty reduction and national welfare are also not possible only by giving materially, empowerment is needed which awakens the community to rise from poverty. Empowerment requires programs and implementers of these programs. Achmad Nuril Mahyudin is an individual and independent humanitarian activist with thirty-three years of experience empowering the poor people of the Ngawi village and has successfully won the prestigious 2014 Indonesian Hero award. He has a community empowerment program that can be adopted by Islamic philanthropic institutions and educational institutions. This qualitative research uses the field research method with the results of community empowerment education from the perspective of Achmad Nuril Mahyudin can fulfill aspects of Islamic Education, aspects of community empowerment and aspects of da’wah bil hal based on the worldview of Islam and the foundation of nation and state. Abstrak Indonesia merupakan negara berkembang anggota Perserikatan Bangsa-Bangsa (PBB) yang turut menyukseskan program Sustainable Development Goals (SDGs) dengan beberapa tujuan untuk kesejahteraan dan pembangunan bangsa termasuk dalam penanggulangan kemiskinan. Dalam pelaksanaannya, pemerintah didukung oleh banyak Lembaga filantropi yang berfokus kepada masing-masing tujuannya. Penanggulangan kemiskinan dan kesejahteraan bangsa juga tidak mungkin hanya dengan pemberian secara materil saja, dibutuhkan pemberdayaan yang membangkitkan masyarakat agar bangkit dari kemiskinan. Pemberdayaan tersebut membutuhkan program dan pelaksana program tersebut. Achmad Nuril Mahyudin merupakan tokoh aktivis kemanusiaan individu dan independen dengan pengalaman tiga puluh tiga tahun memberdayakan masyarakat miskin pedusunan Ngawi dan telah berhasil menyabet penghargaan bergengsi Pahlawan Indonesia 2014. Ia memiliki program pemberdayaan masyarakat yang dapat diadopsi oleh Lembaga filantropi Islam maupun Lembaga pendidikan. Penelitian kualitatif ini menggunakan metode field research dengan hasil pendidikan pemberdayaan masyarakat perspektif Achmad Nuril Mahyudin dapat memenuhi aspek Pendidikan Islam, aspek pemberdayaan masyarakat dan aspek dakwah bil hal dengan berlandaskan the worldview of Islam serta landasan berbangsa dan bernegara.